CRITICAL RACE THEORY: ILLUMINATING CONTEMPORARY ISSUES OF RACIAL INEQUALITY - Mehwish Shahid; Naveed Ahmad Khan; Amina Shehzadi; Dr. Karthiyaini Devarajoo (International Journal of Contemporary Issues in Social Sciences, 2023)
This article examines Critical Race Theory (CRT), a valuable paradigm for understanding and combating racial inequality. We follow CRT’s growth and response to civil rights approaches from its legal scholarship roots. Our focus is on key personalities and legal antecedents who helped it emerge and challenge existing legal paradigms. Examine CRT’s key values, emphasizing structural racism, intersectionality, interest convergence, the voice of color, and liberalism critique. These concepts provide a framework for analyzing systemic racial inequality and societal structures and institutions. The researcher also examines CRT’s current uses in law, education, healthcare, criminal justice, and social activism. CRT’s impact on these issues shows its importance in racial equality. CRT challenges and criticisms include public discourse opposition, limitations, frequent misconceptions, and ongoing controversies. Despite these issues, CRT remains crucial to racial justice discussions. The researcher summarizes major findings, emphasizes CRT’s lasting relevance, and highlights its contributions to social justice and change in the conclusion. We also suggest further study to improve its uses and understanding of racial inequality. This comprehensive Critical Race Theory assessment is useful for scholars, practitioners, policymakers, and those working to end social injustice and racial discrimination.